FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PENJUALAN JASA RENTAL SCAFFOLDING PADA PT. EVCON JAYA NUSANTARA DI PEKANBARU - Sulistiani "; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research was conducted in PT Evcon Jaya Nusantara Pekanbaru. The setting ofthe problem is factors affecting sales volume of scafolding rental service at PT chevron JayaNusantara in Pekanbaru. The purpose of this research was determine the influence of salesvolume and to know efforts are being made to increase the sales of service.The author uses descriptive quantitative analysis methods, and some theories aboutsales volume of service. Collecting data using questionnairs and interviews, the sample usedwas accidental sampling. Source of data used are primary data or data obtained fromquestioners and interviews. Secondary data is data obtained from company documents’ PTEvcon Jaya Nusantara. The results indicate that the influence of internal factors serviceprovided , the availability of items and tightening in providing receivables is very affect salesvolume of service. On external factors changes in consumer tastes and the emergence of newrivals also affect sales volume of service.Key words: sales volume of service, scaffolding.